Penggunaan DO Online pada Pengiriman Barang Impor di Perusahaan Pelayaran - Latifah Dwi Handayani; Nofrisel Nofrisel; Endang Sugiharti (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of this study is to analyse the process and the influence of acceptance in delivery order and lead time delivery order before and after using online delivery order. The rapid development of information, technology, and communication changes human life activities that previously used a manual system to an online system that already applied in ports. It is due to the transparency needed to monitor container position and efficiency of port activities to give accelerate service that can give good impact on logistics cost, container acceptance, and delivery. One of the efforts in accelerating the service is applying electronic or online delivery order for imported goods. This research was conducted at Agility International by using qualitative and quantitative methods. The data was taken from ten shipment companies in a way judgmental sampling through observation, interview, discussion, and monthly report from KPI. The study used paired sample t test. The result shows that the average of lead time for receiving delivery orders before using online delivery order in 2017 was 1.9560 days and after using online delivery order is 0.9800 days.